Educational and labor migration in the new horizons of economic integration in the Eurasian Economic Union - Andronova, Inna V.; Ryazantsev, Sergey V. (Frontiers in Education, 2023)
The paper focuses on clarifying the cause-effect relations of educational and labor migration in implementing the social investment model of economic growth in the Eurasian Economic Union (EAEU). The paper aims to investigate the role of educational and labor migration in implementing the social investment model of economic growth in Russia under the new horizons of economic integration in the EAEU. The authors use the correlation analysis method to determine the role of educational and labor migration in implementing the social investment model of economic growth in the EAEU. The experience of implementing the social investment model of economic growth based on educational and labor migration in the EAEU has been studied using the case study method. The authors present their forecast for implementing the social investment model of economic growth in the EAEU up to 2024. The conditions for developing educational and labor migration in the EAEU in 2022 are determined. The novelty of this research lies in studying educational and labor migration as factors of economic growth in the social investment model in a new perspective of economic integration.